Insights into employee perspectives on corporate social responsibility policies and practices: Embeddedness, participation, and meaningfulness through work - Rodrigues, Susana; Proença, Teresa; Ferreira, Marisa R. (Corporate social-responsibility and environmental management, 2024)
Corporate social responsibility (CSR) has an increasingly important role in organizations, which are taking a proactive stance in the inclusion of concerns and initiatives at this level. This theme has an impact on employees, namely in the meaningfulness through work. Thus, this research aims to assess whether the CSR affect the meaningfulness through work, and whether the degree of incorporation and the design and implementation approach interfere in this relationship. The results, obtained from 235 responses, suggest that it is not CSR policies and practices that impact meaningfulness through work. For this feeling to be achieved, it is necessary for employees to perceive CSR as embedded and the design and implementation of policies and practices to be bottom‐up. In other words, for CSR to lead to real benefits for employees, organizations must make a genuine and substantial commitment to it.